Dating admixture events is unsolved problem in multi-way admixed populations. (19th November 2018) - Chimusa, Emile R; Defo, Joel; Thami, Prisca K; Awany, Denis; Mulisa, Delesa D; Allali, Imane; Ghazal, Hassan; Moussa, Ahmed; Mazandu, Gaston K
Abstract: Advances in human sequencing technologies, coupled with statistical and computational tools, have fostered the development of methods for dating admixture events. These methods have merits and drawbacks in estimating admixture events in multi-way admixed populations. Here, we first provide a comprehensive review and comparison of current methods pertinent to dating admixture events. Second, we assess various admixture dating tools. We do so by performing various simulations. Third, we apply the top two assessed methods to real data of a uniquely admixed population from South Africa. Results reveal that current dating admixture models are not sufficiently equipped to estimate ancient admixtures events and to identify multi-faceted admixture events in complex multi-way admixed populations. We conclude with a discussion of research areas where further work on dating admixture-based methods is needed.